(untitled) - Kolostova, Marianna (Aura musica, 2015)
The author in the paper reflects the view on the artistic activity of the emeritus professor Belo Felix. She deals with the choral composition ``Zazracna komnata'' as a part of the long-term polyesthetic project realised in Bibiana in Bratislava. She presents the brief characteristic of Belo Felix's artistic and compositional process and his activities which overlap, complement and integrate in the concrete projects, as well as in the choral activities for advanced children's choirs.
Keywords: Belo Felix; artistic activity; choral composition; polyesthetic project